3P (Participants, Process and Physical Evidence): Penilaian Konsep, Penerapan, dan Dampaknya Terhadap Tujuan Organisasi Bisnis-Jawa Barat - Harman Malau (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This study aims to investigate the practical application of the 3P variable marketing strategy on business organizations, examine the impact of the 3P variable and identify the order of strength of its impact on the objectives of the business organization. This research uses a leading manufacturing company registered in Bandung-Indonesia. There are 95% of 105 respondents as online primary data distributed through structured questionnaires to the marketing department. Data analysis is performed through valid rates, mean analysis, linear regression and hypothesis testing. The results showed that the variable marketing mix concept applied in the practice of business organizations. The 3P variable is a variable that plays an important role in achieving the goals of business organizations. The correlation of each participant, process and physical evidence is strong and positive, both partially and simultaneously to the goals of the organization. Furthermore, the achievement of organizational goals can be predicted using linear regression. The participant, process and physical evidence variables significantly influence the achievement of organizational goals.